2022
DOI: 10.1111/jssr.12780
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Correlates of Sharing Private Problems in Congregations during the COVID‐19 Pandemic

Abstract: Given the adverse mental health consequences of the COVID‐19 pandemic, it is important to examine whether faith communities continue to provide social and emotional support to members during the pandemic. This study focuses on a particular mechanism through which congregations may help members’ mental health––talking to fellow congregants about private problems. Data for this study come from online surveys conducted between October and December 2020 in 12 congregations (Christian, Jewish, and Hindu) in Washing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
1
2
Order By: Relevance
“…According to our analyses of group differences, this relation appeared to be driven largely by those who identified as belonging to a religious group that is considered a "Minority" in Canada (i.e., Baha ´'ı ´, Buddhist, Hindu, Jewish, Muslim, and Sikh). Although emotional-engagement styles of coping have previously been associated with higher levels of well-being [69,73,77,78] our study revealed that emotionalengagement coping was instead associated with more negative mental and physical health outcomes. Although our emotional-engagement factor included strategies such as emotionalexpression and social support-seeking, which could have beneficial actions [54,77,78], it also included rumination, other-blame, and wishful thinking-strategies that are generally considered to be less "adaptive" in coping with stress [79,80].…”
Section: Plos Onecontrasting
confidence: 77%
See 2 more Smart Citations
“…According to our analyses of group differences, this relation appeared to be driven largely by those who identified as belonging to a religious group that is considered a "Minority" in Canada (i.e., Baha ´'ı ´, Buddhist, Hindu, Jewish, Muslim, and Sikh). Although emotional-engagement styles of coping have previously been associated with higher levels of well-being [69,73,77,78] our study revealed that emotionalengagement coping was instead associated with more negative mental and physical health outcomes. Although our emotional-engagement factor included strategies such as emotionalexpression and social support-seeking, which could have beneficial actions [54,77,78], it also included rumination, other-blame, and wishful thinking-strategies that are generally considered to be less "adaptive" in coping with stress [79,80].…”
Section: Plos Onecontrasting
confidence: 77%
“…Although emotional-engagement styles of coping have previously been associated with higher levels of well-being [69,73,77,78] our study revealed that emotionalengagement coping was instead associated with more negative mental and physical health outcomes. Although our emotional-engagement factor included strategies such as emotionalexpression and social support-seeking, which could have beneficial actions [54,77,78], it also included rumination, other-blame, and wishful thinking-strategies that are generally considered to be less "adaptive" in coping with stress [79,80]. In fact, rumination itself has been associated with diverse psychological disturbances and predicted the later development of depression [81].…”
Section: Plos Onecontrasting
confidence: 77%
See 1 more Smart Citation